O desenvolvimento do sport education numa instituição cultural e suas implicações para o ensino do esporte: estudo de caso - Brasil, Tainara Caroline Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The current scenario that contemplates the Pedagogy of Sport, walks so that the process of teaching and learning sports is developed from the perspective of the subject, requiring a more effective participation of those who practice. Along these lines, this work aimed to analyze the implications of Sport Education for the teaching of Sport from the perspective of a Physical Education Professional. For this, the methodological approach used was qualitative, characterized by a case study. Thus, data collection was performed through a structured interview with a Physical Education Professional, who acted as a physical activity instructor in a cultural institution in the interior of São Paulo. The information was analyzed, considering the relevant elements throughout the speech, fostering the development of the axes of analysis Autonomy; Understanding of sports practice and Teaching context. The results pointed out, therefore, that Sport Education implies the incentive for a more autonomous behavior of the participants, with emphasis on their protagonism and mediating role of the Physical Education professional; relevance for a broader understanding of sports practice, based on the planning elements; game; understanding of the modality; effective participation and this model as a possibility in the teaching of sport and for the knowledge of the teaching context, considering characteristics that make up both the scenario of sports practice and the professional scenario.

O cenário atual que contempla a Pedagogia do Esporte, caminha para que o processo de ensino e aprendizagem esportivo seja desenvolvido pela ótica do sujeito, exigindo uma participação mais efetiva de quem pratica. Nesta linha, o presente trabalho teve como objetivo analisar as implicações do Sport Education para o ensino do Esporte sob a perspectiva de um Profissional de Educação Física. Para isto, a abordagem metodológica utilizada foi qualitativa, caracterizada por estudo de caso. Desse modo, a coleta de dados foi realizada por meio de entrevista estruturada com um Profissional de Educação Física, que atuava enquanto instrutor de atividade física numa instituição cultural do interior de São Paulo. As informações foram analisadas, considerando os elementos relevantes ao longo do discurso, fomentando a elaboração dos eixos de análise Autonomia; Compreensão da prática esportiva e Contexto de ensino. Os resultados apontaram, portanto, que o Sport Education implica no incentivo para um comportamento mais autônomo dos participantes, com ênfase em protagonismo destes e papel mediador do profissional de Educação Física; relevância para a compreensão mais ampla da prática esportiva, com base nos elementos planejamento; jogo; entendimento da modalidade; participação efetiva e deste modelo enquanto possibilidade no ensino do esporte e para o conhecimento do contexto de ensino, considerando características que compõem tanto o cenário da prática esportiva quanto o cenário profissional.
Keywords: Educação fisica; Esportes e educação; Autonomia; Sports